Molecular epidemiology and virulence of goose astroviruses genotype-2 with different internal gene sequences - Xu, Linhua; Jiang, Bowen; Cheng, Yao; Gao, Zhenjie; He, Yu; Wu, Zhen; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; et al. (Frontiers in Microbiology, 2023)
Goose astrovirus (GAstV) is a small, non-enveloped, single-stranded, positive-sense RNA virus. GAstV has rapidly spread across various regions in China since 2016. In Sichuan, out of 113 samples were collected from goose diseases between 2019 and 2022, 97 were positive for GAstV through PCR testing. Remarkably, over the past three years, GAstV outbreak in Sichuan has accounted for an astonishing 85.8% of all goose-origin viruses. Among these cases, 63.9% had single GAstV infections, 29.9% had dual infections, and 6.2% had quadruple infections. To comprehend the variations in virulence among distinct strains of GAstV. 12 representative strains of single GAstV infections were isolated. These strains exhibited distinct characteristics, such as prominent white urate depositions in organs and joints, as well as extensive tissues phagocytosis in major target organs’ tissues. The conserved ORF1b genes and the variable ORF2 genes of these representative GAstV strains were sequenced, enabling the establishment of phylogenetic trees for GAstV. All GAstV strains were identified as belonging to genotype-2 with varying internal gene sequences. Experiments were conducted on GAstV genotype-2, both in vivo and in vitro, revealed significant variations in pathogenicity and virulence across susceptible cells, embryos, and goslings. This comprehensive study enhances researchers’ understanding of the transmission characteristics and virulence of GAstV genotype-2, aiding in a better comprehension of their molecular epidemiology and pathogenic mechanism.